Effects of concurrent training on cardiorespiratory fitness and body composition in adults with schizophrenia: CORTEX-SP study. (11th May 2022) - Tous-Espelosin, M; Iriarte-Yoller, N; Sanchez, P; Maldonado-Martin, S
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Spanish Ministry of Economy and Competitiveness "Fondo de Investigación Sanitaria del Insti-tuto de Salud Carlos III" Background: Concurrent training (i.e. a combination of aerobic and resistance exercise in the same session) is emerging as a time-efficient exercise strategy for improving cardiorespiratory fitness and controlling body composition parameters. Purpose: The purpose of this study was to determine the effectiveness of a concurrent exercise program on cardiorespiratory fitness and body composition in adults with schizophrenia (SP). Methods: Participants (n=98, 20.4% women, 41.4±10.1 yr old) with SP were randomly assigned into an attention control group (usual care) or a supervised exercise group (concurrent training, 3 days/week). All variables were assessed pre- and post-intervention (20 weeks). For the assessment of cardiorespiratory fitness, a peak cardiopulmonary exercise test on a cycle ergometer and the Modified Shuttle Walk Test (MSWT) were used. Results: Following the intervention, in the control group, there was a significant (P <0.05) increased in body mass (Δ = 2.54%), body mass index, BMI (Δ = 2.82%), waist circumference (Δ = 2.70%) and a decreased in MSWT (Δ = - 7.54%). However, in the exercise group, there was a significant (P<0.001) increased in first ventilatory threshold, VT1 (Δ = 28.69%), peak oxygen uptake, V̇O2peak (L∙min-1) (Δ = 19.58%), V̇O2peak (mL∙kg.1∙min-1) (Δ = 21.52%) and MSWT-distance (Δ = 11.43%), with no significant changes in body composition (P>0.05). When both groups were compared, body mass, and BMI was significantly (P<0.05) more reduced, and VT1, V̇O2peak, and MSWT more increased in the exercise group. Conclusion: A supervised concurrent exercise program in people with SP helps to maintain body composition values and leads to improvements in cardiorespiratory fitness levels. Exercise should be considered as a co-adjuvant program in the treatment of population with SP.